2016
DOI: 10.1016/j.clon.2016.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy and Immunotherapy Combinations in Non-small Cell Lung Cancer: A Promising Future?

Abstract: Abstract.Abstract: The goal of re-programming the host immune system to target malignancy with durable antitumour clinical responses has been speculated for decades. In the last decade such speculation has been transformed into reality with unprecedented and durable responses to immune checkpoint inhibitors seen in solid tumours. This mini-review considers the mechanism of action of immune modulating agents and the potential for combination with radiotherapy in the treatment of non-small cell lung cancer.Intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…In a small cohort of patients with skin and kidney cancer, stereotactic body radiotherapy with high dose IL2 showed better tumor response rates over that of IL2 alone [19]. There are several Phase I and 2 clinical trials ongoing in patients with NSCLC for evaluation of radiotherapy with PD-PDL1 immune checkpoint inhibitors, pembrolizumab, and nivolumab [20], outlined in Table 1.…”
Section: Combinatorial Approaches To Enhance Pd1-pdl1 Blockadementioning
confidence: 99%
“…In a small cohort of patients with skin and kidney cancer, stereotactic body radiotherapy with high dose IL2 showed better tumor response rates over that of IL2 alone [19]. There are several Phase I and 2 clinical trials ongoing in patients with NSCLC for evaluation of radiotherapy with PD-PDL1 immune checkpoint inhibitors, pembrolizumab, and nivolumab [20], outlined in Table 1.…”
Section: Combinatorial Approaches To Enhance Pd1-pdl1 Blockadementioning
confidence: 99%
“…интерферона I типа, увеличение главного комплекса гистосовместимости, экспрессию неоантигенов и индукцию иммуногенной смерти клеток [24][25][26][27]. Другие элементы иммунной модуляции включают изменения в механизме представления антигена и транслокации кальретикулина на поверхности клетки [28].…”
Section: Reviews Of Literatureunclassified
“…Recent preclinical and clinical studies have led to interest in the potential of RT to improve the efficacy of concurrent or subsequent immunotherapy . A phase III study demonstrated that durvalumab, a PD‐1 ligand inhibitor, administered after a combination of RT and chemotherapy for locally advanced lung cancer led to a significantly longer progression‐free survival (PFS) .…”
Section: Introductionmentioning
confidence: 99%